Perioperative factors predicting delayed enteral resumption and hospital length of stay in cytoreductive surgery with hyperthermic intraperitoneal chemotherapy: Retrospective cohort analysis from a single centre in India - Kalpana Balakrishnan; Nivedhyaa Srinivasaraghavan; Meenakshi V Venketeswaran; Thendral Ramasamy; Ramakrishnan A Seshadri; E Hemanth Raj (Indian Journal of Anaesthesia, 2020)
Background and Aims: Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is an extensive procedure associated with significant morbidity, delay in return of gastrointestinal function and discharge from hospital. Our aim was to assess perioperative factors influencing enteral resumption (ER) and length of stay in the hospital (LOS) in CRS-HIPEC. Methods: A retrospective analysis was conducted in a major tertiary cancer centre. Sixty-five patients who underwent CRS-HIPEC between July 2014 and March 2019 were included in the study. The perioperative data were collected from patient records. The primary outcome measure was day of oral resumption of 500 ml of clear fluids and secondary outcome was the LOS. Univariate and multivariate logistic regression analysis was done for the various continuous and categorical perioperative variables for both ER and LOS to elicit the magnitude of risk for both outcomes. Results: Univariate logistic regression revealed that peritoneal carcinomatosis index score (PCI), duration of surgery, blood loss and postoperative ventilation influenced both ER and LOS. Serum albumin, plasma usage and total peritonectomy affected only the LOS but not ER. Multivariate analysis showed that duration of surgery (P = 0.006) and quantum of intravenous fluid infused (P = 0.043) were statistically associated with ER, while serum albumin level (P = 0.025) and postoperative ventilation (P = 0.045) were independently predictive of LOS. Conclusion: CRS-HIPEC is an extensive surgery and multiple factors are associated with ER; of these, duration of surgery and intraoperative fluid therapy are significant factors. Low serum albumin and prolonged postoperative ventilation are associated with increased LOS.